2010
DOI: 10.1097/ta.0b013e3181efc6c6
|View full text |Cite
|
Sign up to set email alerts
|

Ground Level Falls Are Associated With Significant Mortality in Elderly Patients

Abstract: Patients older than 70 years and with GCS score <15 represent a group with significant inhospital mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
174
6
10

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 207 publications
(206 citation statements)
references
References 14 publications
16
174
6
10
Order By: Relevance
“…The incidence of lesions to the head segment is significant, as well as fractures of extremities 12 . The mortality rate is higher than in younger individuals, especially in the presence of concomitant diseases and the need for specific treatment [12][13][14] . In a previous study we compared patients aged above and below 60 years and observed a higher incidence of severe intracranial lesions, such as subdural hematomas, cerebral contusions and subarachnoid hemorrhage in the group of patients with more advanced age 14 …”
Section: Discussion Discussion Discussion Discussion Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The incidence of lesions to the head segment is significant, as well as fractures of extremities 12 . The mortality rate is higher than in younger individuals, especially in the presence of concomitant diseases and the need for specific treatment [12][13][14] . In a previous study we compared patients aged above and below 60 years and observed a higher incidence of severe intracranial lesions, such as subdural hematomas, cerebral contusions and subarachnoid hemorrhage in the group of patients with more advanced age 14 …”
Section: Discussion Discussion Discussion Discussion Discussionmentioning
confidence: 99%
“…The most common traumas mechanisms are falling from the standing and trampling 12 . The incidence of lesions to the head segment is significant, as well as fractures of extremities 12 .…”
Section: Discussion Discussion Discussion Discussion Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study of GLF in elderly patients focused on the epidemiology and risk factors for in-patient deaths after GLF using the national trauma data bank of the American College of Surgeons [3]. The study reported that patient age >70 years, with GCS score<15 were at significant risk of in-patient mortality after GLF.…”
Section: Introductionmentioning
confidence: 99%
“…GLF has becomes a leading mechanism of injury in the elderly [2]. Although GLF has been traditionally considered a lowenergy mechanism of injury it has become a significant risk factor for morbidity and mortality among the elderly with 38-47% of those who fall will eventually have a fatal outcome [3]. Furthermore, one-half of those who fall are likely to fall again [4].…”
Section: Introductionmentioning
confidence: 99%